Exomala (Neoblitopertha) campestris (Latreille, 1804) and Exomala (Neoblitopertha) succincta (Castelnau, 1840): two distinct European species (Coleoptera, Scarabaeidae, Rutelinae, Anomalini). - Rössner, Eckehard; Zorn, Carsten; Branco, Tristao (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Evidence is presented showing that, according to the Code, Melolontha campestris Latreille, 1804, albeit a junior primary homonym of Melolontha campestris Herbst, 1783 must to be used as the valid name for the species currently known as Exomala (Neoblitopertha) campestris. Exomala (Neoblitopertha) succincta (Castelnau, 1840), currently considered synonym of Exomala (Neoblitopertha) campestris (Latreille, 1804), is rehabilitated as a good species. Diagnostic features enabling the separation of succincta from campestris are provided, as well as a key to the species of Neoblitopertha Baraud, 1991.KeywordsTaxonomy, nomenclature, new synonymy, key to species, Coleoptera, Scarabaeidae, Anomalini, Exomala (Neoblitopertha), Palaearctic region.Nomenclatural Actscampestris (Latreille, 1804) (Exomala (Neoblitopertha)), nom. protectum over Melontha campestris Herbst, 1783: nom. oblitumsuccincta (Castelnau, 1840) (Exomala (Neoblitopertha)), stat. rev. hitherto a synonym of Exomala (Neoblitopertha) campestris (Latreille, 1804)abbreviata Mulsant, 1842 (Phyllopertha campestris var.), syn. n. of Exomala (Neoblitopertha) succincta (Castelnau, 1840)cruciata Mulsant, 1842 (Phyllopertha campestris var.), syn. n. of Exomala (Neoblitopertha) succincta (Castelnau, 1840)maculata Mulsant, 1842 (Phyllopertha campestris var.), syn. n. of Exomala (Neoblitopertha) succincta (Castelnau, 1840)pauperata Mulsant, 1842 (Phyllopertha campestris var.), syn. n. of Exomala (Neoblitopertha) succincta (Castelnau, 1840)